The magnificent Ambersons - Tarkington, Booth 1869-1946 (Modern Library, 1998)
Winner of the Pulitzer Prize when it was first published in 1918. The Magnificent Ambersons chronicles the changing fortunes of three generations of an American dynasty. The protagonist of Booth Tarkington's great historical drama is George Amberson Minafer, the spoiled and arrogant grandson of the founder of the family's magnificence. Eclipsed by a new breed of developers, financiers, and manufacturers, this pampered scion begins his gradual descent from the midwestern aristocracy to the working class